Spontaneous coronary artery dissection and fibromuscular dysplasia: insights into recent developments - Eltabbakh, Ayah; Khudair, Ahmed; Khudair, Aiman; Fredericks, Salim (Frontiers in Cardiovascular Medicine, 2024)
Spontaneous coronary artery dissection (SCAD) is uncommon cause of acute coronary syndrome and is a poorly understood disease predominantly affecting females. It is characterized by an abrupt separation in the coronary arterial wall due to intramural bleeding. Fibromuscular dysplasia (FMD) is a non-atherosclerotic arteriopathy manifesting in medium and small-sized arteries. It is a concomitant disease among SCAD patients. FMD prevalence in SCAD patients is up to 86%, which can be explained through varying screening modalities. The potential association has been elucidated in some studies; not only has a genetic link been recently delineated between SCAD and FMD, but there is data to suggest that FMD can predispose to SCAD and can also be a potential predictor of its recurrence. However, further investigations are required due to conflicting reports in literature. To further dive into its pathology, it is crucial to highlight the importance of systematic screening in SCAD to identify risk factors and to be used to detect FMD in such patients. The two pathologies pose unique challenges in understanding its pathophysiology, diagnosis and management, as there is no evidence of a definitive treatment. Physical exercise is a potential beneficial treatment, which is understudied in the long-term approach to treatment for patients with both diseases. Limited research brings disadvantages to the understanding of their association, to give rise to better management recommendations. This mini-review aims to highlight the recent developments in the association between SCAD and FMD, its potential genetic association and some insights in screening, diagnosis, and management.